GENETIC VARIABILITY, CORRELATION AND PATH ANALYSIS IN POTATO (Solanum tuberosum L.) (Bangladesh Journal of Plant Breeding and Genetics, 2007)
Genotypic and phenotypic variability, heritability, genetic advance, correlation coefficients and path coefficients analysis were done for yield and its contributing characters in 28 genotypes of potato. High heritability coupled with high genetic advance as percent of mean and high genotypic coefficients of variation were observed for number of tubers per plant, yield per plant and average weight of a tuber suggesting selection for these traits would give good response. Genotypic and phenotypic correlation of the number of tubers per plant and weight of tubers per plant were highly significant. Plant vigour, number of compound leaves per plant and number of tubers per plant, average weight of a tuber and dry matter content of tuber had high degree of positive association with tuber yield per plant. As per path analysis, average weight of tuber and total number of tubers per plant contributed maximum direct effect to tuber yield indicating their importance as selection index for yield improvement.DOI: http://dx.doi.org/10.3329/bjpbg.v20i1.17023